Plasma microRNAs are associated with atrial fibrillation and change after catheter-ablation (the miRhythm Study) - McManus, David D. (Heart Rhythm, 2014)
BACKGROUND: MicroRNAs (miRNAs) are associated with cardiovascular disease (CVD), control gene expression, and are detectable in the circulation. OBJECTIVE: To test the hypothesis that circulating miRNAs would be associated with atrial fibrillation (AF). METHODS: Using a prospective study design powered to detect subtle differences in miRNAs, we quantified plasma expression of 86 miRNAs by high-throughput quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) in 112 participants with AF and 99 without AF. To examine parallels between cardiac and plasma miRNA profiles, we quantified atrial tissue and plasma miRNA expression using qRT-PCR in 31 participants undergoing surgery. We also explored the hypothesis that lower AF burden after ablation would be reflected in the circulating blood pool by examining change in plasma miRNAs after AF ablation (n=47). RESULTS: The mean age of the cohort was 59 years. 58% of participants were men. Plasma miRs-21 and 150 were 2-fold lower in participants with AF than in those without AF after adjustment (p ≤ 0.0006). Plasma levels of miRs-21 and 150 were also lower in participants with paroxysmal AF than in those with persistent AF (p <0.05). Expression of miR-21, but not miR-150, was lower in atrial tissue from patients with AF compared to no AF (p<0.05). Plasma levels of miRs-21 and 150 increased 3-fold after AF ablation (p ≤ 0.0006). CONCLUSIONS: Cardiac miRs-21 and 150 are known to regulate genes implicated in atrial remodeling. Our findings show associations between plasma miRs-21 and 150 and AF, suggesting that circulating miRNAs provide insights into cardiac gene regulation.